2018
DOI: 10.1088/1367-2630/aae28f
|View full text |Cite
|
Sign up to set email alerts
|

Off-diagonal observable elements from random matrix theory: distributions, fluctuations, and eigenstate thermalization

Abstract: We derive the eigenstate thermalization hypothesis (ETH) from a random matrix Hamiltonian by extending the model introduced by Deutsch (1991 Phys. Rev. A 43 2046). We approximate the coupling between a subsystem and a many-body environment by means of a random Gaussian matrix. We show that a common assumption in the analysis of quantum chaotic systems, namely the treatment of eigenstates as independent random vectors, leads to inconsistent results. However, a consistent approach to the ETH can be developed by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 53 publications
(139 reference statements)
6
76
0
Order By: Relevance
“…This is a very common assumption in the treatment of random matrices [37], and is well justified numerically for this model in [31].…”
Section: B Random Matrix Modelmentioning
confidence: 80%
See 1 more Smart Citation
“…This is a very common assumption in the treatment of random matrices [37], and is well justified numerically for this model in [31].…”
Section: B Random Matrix Modelmentioning
confidence: 80%
“…Despite much recent progress on the understanding of thermalization, there has been less work describing the decay process [26][27][28] or the timescales of equilibration [29]. We address both of these using a Random Matrix Theory (RMT) model [16,30], which the current authors have recently shown reproduces the ETH ansatz [31]. We describe the decay to equilibrium of generic nonintegrable quantum systems, and obtain an expression for the time-averaged fluctuations of local observables in terms of their rate of decay to equilibrium; thus observing an emergent classical Fluctuation-Dissipation Theorem (FDT), analogous to those derived from a Langevin * Electronic address: C.Nation@sussex.ac.uk † Electronic address: D.Porras@iff.csic.es equation for Brownian motion.…”
Section: Introductionmentioning
confidence: 99%
“…Our theory, developed in Ref. [38] by extending Deutch's RMT model [39][40][41], can be used to obtain arbitrary correlation functions c µ (α)c ν (α) · · · V , where · · · V denotes the ensemble average over an ensemble of random matrix perturbations, V , for a N × N Hamiltonian of the form (2), with (H 0 ) αβ = αω 0 δ αβ , with ω 0 = 1 N and V a random matrix selected from the GOE, with V 2 αβ V = (1+δ αβ )g 2 N . We showed that these may be expressed as sums of products of four-point correlation functions, given by (for µ = ν),…”
Section: B Main Resultsmentioning
confidence: 99%
“…where ρ µν = ψ µ |ρ|ψ ν , and (σ z ) µν = ψ µ |σ z |ψ ν . We assume that V is well approximated by a random matrix and build on a statistical theory for the manybody wave-functions [38],…”
Section: A Set Upmentioning
confidence: 99%
See 1 more Smart Citation